Penggunaan Media Sosial Terhadap Partisipasi Mahasiswa Ilmu Komunikasi UNJ dalam Menentukan Capres dan Cawapres 2019 - Annisa Sekarwulan; Assyifa Amelia Azzahra; Nada Syifafasya; Dini Safitri (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to describe the use of social media on the attitude of UNJ students in determining the 2019 Presidential and Vice Presidential Candidates. The method used in this study is qualitative by using an interaction model consisting of data reduction, data presentation and conclusions. Data collection techniques used in this study were interviews, observation and documentation with three informants as resource persons. The results showed that social media is not a reason in determining the choice of 2019 presidential and vice presidential candidates. That is because each individual has their own political views. Social media is used as a means of finding information about 2019 presidential and vice presidential candidates. Information that is often obtained on social media is a work program, vision and mission. Usually the information uploaded by the 2019 presidential and vice presidential candidates is easy to understand because it uses language that is easy to remember and understand. But there is some information that must be further studied. In addition, social media can become one of the effective media in accommodating the aspirations of the community if the presidential and vice presidential candidates can respond to the message conveyed by the public.